The principles of international civil procedure (Journal of actual problems of jurisprudence, 2018)
It is well known that each branch has its own principles, that constitute the normative, substantive core of the legal system, and that all legal requirements of the normative and individual character must adhere to these principles. Legal principles form the basis of any branch and not only serve as a distinctive feature of a branch, but also indicate the presence of a branch as a whole. In this article the author considers the principles of international civil procedure, as well as their formation and types. On the basis of analysis of general legal principles an attempt is made to define the principles of international civil procedure, their types and functions. Key words: international civil procedure, branch of law, principle.